2019
DOI: 10.1016/j.bjpt.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity, dynapenia and dynapenic-abdominal obesity as factors associated with falls

Abstract: Objective: To investigate whether abdominal obesity, dynapenia and dynapenic-abdominal obesity are associated to the prevalence of single or recurrent falls in older adults. Methods: We analyzed data from 1,046 community-dwelling participants of the SABE Study (Saúde, Bem-estar e Envelhecimento/Health, Well-Being and Ageing). Participants were classified as non-dynapenic/non-abdominal obese, abdominal obese only, dynapenic only, and dynapenic-abdominal obese based on waist circumference (>102 cm for men and >8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 51 publications
7
47
1
4
Order By: Relevance
“…A total of N = 37,124 individuals (66% women) aged 50 to 94 years were included. Eight studies included women only, 20,22,24,26,27,30,42,44 two included men only, 14,25 and 16 included both men and women 21,23,28,29,31–41,43 . Twenty studies were cross‐sectional in design, 20,22–25,28–38,41–44 and six studies were cohort studies 14,21,26,27,39,40 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of N = 37,124 individuals (66% women) aged 50 to 94 years were included. Eight studies included women only, 20,22,24,26,27,30,42,44 two included men only, 14,25 and 16 included both men and women 21,23,28,29,31–41,43 . Twenty studies were cross‐sectional in design, 20,22–25,28–38,41–44 and six studies were cohort studies 14,21,26,27,39,40 .…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies included women only, 20,22,24,26,27,30,42,44 two included men only, 14,25 and 16 included both men and women 21,23,28,29,31–41,43 . Twenty studies were cross‐sectional in design, 20,22–25,28–38,41–44 and six studies were cohort studies 14,21,26,27,39,40 . Twenty‐five studies included community‐dwelling older adults, 14,20–35,37–44 and one study was conducted in hospitalized older adults 36 .…”
Section: Resultsmentioning
confidence: 99%
“…However, without previous studies, it is difficult to draw some parallel [56]. Different clinical outcomes, such as increased risk of developing metabolic syndrome, difficulties in performing daily living activities of and mortality are related to muscle mass and low quality of muscle functions [35,68,69]. Recent evidence shows that low quality muscle mass is associated with the development of frailty in obese individuals [70].…”
Section: Discussionmentioning
confidence: 99%
“…Souza Barbosa and colleagues [ 10 ] based on a 4-year follow-up study pointed out that abdominal obesity significantly increased the risk of mobility disability within a population aged 64 to 74 years. Moreover, abdominal obesity accompanied with dynapenia (known as dynapenic abdominal obesity) significantly increase the risk of single fall among elderly people [ 11 ]. Nevertheless, a consistent finding from the previous review suggested that abdominal obesity in elderly people threatens their walking, stair-climbing, and chair-rise abilities, subsequently reducing their quality of life [ 12 ].…”
Section: Introductionmentioning
confidence: 99%